An investigation on the international tourists’ expenditures in Thailand: a modelling approach - Sriboonchitta, Songsak; Chaiboonsri, Chukiat; Chaitip, Prasert; Chaitip, Arreyah; Kovács, Sándor; Balogh, Péter (Applied Studies in Agribusiness and Commerce, 2013)
As a result of the increase in both the international tourists’ expenditures and tourist arrivals to Thailand, there is a growing interest in determining the trend of international tourists’ expenditures based on time-series modelling. In our article secondary data were used to produce forecasts of the international tourists’ expenditures in Thailand between 2009 and 2010. The forecasting method is based on the ARFIMAX (0, 0.197, 0, 0.033) model. Furthermore, this method predicted that international tourists’ expenditures in Thailand between 2009 and 2010 will have to contract and slow down. This paper seeks to determine whether the international tourists’ expenditures are affected by other circumstances. The results of this study revealed that the international tourist arrivals to Thailand will also have to slow down. However, from the results, there is solid evidence to support such a claim.